Evidence-Based Screening and Assessment: A Randomized Trial of a Validated Assessment Tool in Three New York City Drug Courts, 2011-2015 - Rempel, Michael ([Verlag nicht ermittelbar], 2022)
With funding from the National Institute of Justice, the Center for Court Innovation examined the impact of introducing an evidence-based risk-need assessment and treatment matching protocol into three New York City drug courts. Preexisting practice in all three sites involved administration of a non-validated bio-psychosocial assessment, whose results informed the professional judgment of court-employed case managers, but without the aid of a structured decision making system.